Pengelolaan Sumber Daya Manusia Pada Usaha Mikro Oleh-oleh Khas Balikpapan - Nur Vita Oppu; Ida Suriana; Ramli Ramli (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2019)
This study describes human resource management in micro business of gifts and handicrafts. The sample of this study was 70 typical micro-businesses in Balikpapan. Management of human resources is one of the important aspects to be able to develop a business unit .This research is intended to get an idea of how to manage the human resources of a micro business unit. The results of the study found that management was still carried out informally.Training for employees is not done on an ongoing basis, there are still giving compensation and work safety programs are not conducted regularly, providing extrinsic motivation is good enough already.